Aspek Pendukung Affirmative Action Perempuan pada Anggota Bawaslu Provinsi dan Kabupaten/Kota di Jawa Timur - Yon Daryono (Jurnal Adhyasta Pemilu, 2021)
A policy of women's representation (affirmative action) in organizing elections (Elections) becomes essential. The representation of women as election supervisors is still very minimal and has not reached a quota of 30 percent despite the law, Particularly at the province, district, and city levels. In this research, women members of Bawaslu Province in Indonesia and women members of Bawaslu regencies/cities in East Java became the object of study. What aspects support them being elected as members of Bawaslu provinces and districts/cities become the subject of the problem that will be examined. Qualitative research methods are used to answer this research problem. Data collection techniques use literature study books, offline and online scientific journals, news, websites, youtube recordings, which are then critically analyzed with Hanna F Pitkin's representation theory. The representation of affirmative action in Indonesia's Bawaslu province was concluded based on the findings of the study and debate. Four things have supported Bawaslu regency/city in East Java. First, the education aspect. Second, the background of activities and professions before becoming a member of Bawaslu. Third, ownership knowledge as a former election organizer of Adhoc and KPU, and Bawaslu. Fourth, support operational experience in PMII, HMI, and organizations.